The nautical mile - Moody, Alton B. (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 1950 in The International Hydrographic Review (IHR, https://ihr.iho.int/): Moody, A. B. (1950). The nautical mile. The International Hydrographic Review, 27(1), 77–85. https://journals.lib.unb.ca/index.php/ihr/article/view/26967 Reproduced with variants and with the Author’s and Editor’s permission from an article published in the United States Naval Institute Proceedings, Vol. 75, Nº 11, Annapolis, November 1949, page 1257.